2017
DOI: 10.1051/0004-6361/201731566
|View full text |Cite
|
Sign up to set email alerts
|

The ortho-to-para ratio of H2Cl+: Quasi-classical trajectory calculations and new simulations in light of new observations

Abstract: Multi-hydrogenated species with proper symmetry properties can present different spin configurations, and thus exist under different spin symmetry forms, labeled as para and ortho for two-hydrogen molecules. We investigated here the ortho-to-para ratio (OPR) of H 2 Cl + in the light of new observations performed in the z=0.89 absorber toward the lensed quasar PKS 1830−211 with the Atacama Large Millimeter/submillimeter Array (ALMA). Two independent lines of sight were observed, to the southwest (SW) and northe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
(96 reference statements)
1
2
0
Order By: Relevance
“…In particular, (1) the deuteration ratios within the central few thousand astronomical units predicted by the proton-hop model are in very good agreement with the observed values ( 0.4, 0.2 and 0.06 for NH 2 D/NH 3 , NHD 2 /NH 2 D and ND 3 /NHD 2 , respectively; see §2); (2) the ortho-to-para ratios of NH 2 D and NHD 2 are also in better agreement with observations, with the first one increasing and the second one decreasing, as required by the analysis of Harju et al [46]. Although a proper line radiative transfer analysis needs to be carried out to quantify the agreement between model predictions and observations, overall we can conclude that proton hop appears to be a better representation of nuclear spin-state chemistry, in agreement with the conclusion of Le Gal et al [47].…”
Section: Scrambling or Proton Hop?supporting
confidence: 85%
See 1 more Smart Citation
“…In particular, (1) the deuteration ratios within the central few thousand astronomical units predicted by the proton-hop model are in very good agreement with the observed values ( 0.4, 0.2 and 0.06 for NH 2 D/NH 3 , NHD 2 /NH 2 D and ND 3 /NHD 2 , respectively; see §2); (2) the ortho-to-para ratios of NH 2 D and NHD 2 are also in better agreement with observations, with the first one increasing and the second one decreasing, as required by the analysis of Harju et al [46]. Although a proper line radiative transfer analysis needs to be carried out to quantify the agreement between model predictions and observations, overall we can conclude that proton hop appears to be a better representation of nuclear spin-state chemistry, in agreement with the conclusion of Le Gal et al [47].…”
Section: Scrambling or Proton Hop?supporting
confidence: 85%
“…This disagreement between model predictions and observations indicates that our basic assumption of complete scrambling may not be correct. Indeed, Le Gal et al [47] recently performed an observational and theoretical study of H 2 Cl + , finding that its major formation reaction (HCl + + H 2 → H 2 Cl + + H) produces this ion via a hydrogen abstraction rather than a scrambling mechanism. Inspired by these recent findings, we modified our model to eliminate the full scrambling assumption from Sipilä et al [37] model and include instead the proton hop mechanism.…”
Section: Deuteration Of Ammonia In Quiescent Dense Cloudsmentioning
confidence: 99%
“…Second, the existence of nuclear-spin selection rules in chemical reactions, as predicted theoretically by Quack (1977), has been demonstrated experimentally in ion-neutral reactions involving H + 3 (Uy, Cordonnier & Oka 1997;Crabtree et al 2011b). The nuclear-spin chemistry of interstellar molecules has gained interest in recent years and detailed models have been dedicated to the OPR of NH 3 (Faure et al 2013;Le Gal et al 2014), H + 3 and its deuterated isotopologues (Albertsson et al 2014;Harju et al 2017b), deuterated ammonia (Harju et al 2017a), H 2 O + (Herbst 2015) and H 2 Cl + (Neufeld et al 2015;Le Gal et al 2017). These studies have shown that the OPR of molecules formed in the gas phase can be significantly lower than the statistical (hightemperature limit) values and is entirely controlled by chemical selection rules.…”
mentioning
confidence: 95%